Perancangan Sistem Informasi Pendataan Pelayanan Ibu Hamil Pada Puskesmas Sorong Timur Kota Sorong: Pregnant Women's Services - Iriene Surya Rajagukguk (JURNAL PETISI (Pendidikan Teknologi Informasi), 2023)
Puskesmas Sorong Timur is one of the community health service centers located in Sorong City, West Papua. The recording of pregnant women's data at the Puskesmas is still fairly manual using books and is quite a lot, and it increases every year. Puskesmas requires an information system for collecting information on pregnant women's services. The research methods applied are data collection methods, namely primary data (interviews, and observations) and secondary data (books, theses, journal references, internet media). The system development method is the prototype method. Software used XAMPP, Sublime Text 3, Microsoft Visio 2007, Rational Rose 7, Balsamic Mockup 3, UC Browser. The results of this study display the Main Page of the Website, Login Page, Data Page of Pregnant Women, Admin Page, etc. It can be concluded that the Information System for Data Collection of Pregnant Women Services at the East Sorong Health Center is expected to make it easier to find data on pregnant women and also in presenting the information produced more accurately and on time, making it easier to provide information to the Puskesmas Management and related parties and can facilitate the process of processing baby data and making reports. The advice given in order to improve the quality of the website that has been built in the future will add new features if needed later.